Pelaksanaan Program Kerja dalam Kegiatan KKN Mandiri Universitas Flores di Kelurahan Paupire - Marselina, Apriana; Ismail, Nuraini; Djou, Laurentius Dominicus Gadi; Nona, Fitri Rohaini (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
The real work-study program (KKN) is one of the programs of the University of Flores as one of the implementations of the Tri Dharma of Higher Education, namely student service to the community to help and guide the community in utilizing resources that are expected to help develop the potential of the community. This program is carried out by aligning community service activities among lecturers and students and still bringing together the values of togetherness at the University of Flores. This program is expected to be a means to assist students in applying real and reliable knowledge so that it can provide value and benefits to society in developing their entrepreneurship. The implementation of KKN starts from 03 August to 03 September 2020 in the Paupire Family, Ende Tengah District, Ende Regency. Activities and work programs are carried out during the implementation of the Community Service Program in Paupire Village, Central Ende District, starting from Paupire Village to carry out Real Work Lectures (KKN) in that place. Planning a work program in the Paupire village, Central Ende District during the Community Service Program (03 August to 03 September 2020). Carry out activities and work programs related to the Entrepreneurship theme that have been planned during the KKN Mandiri. Doing community service with KKN students and village employees at the Paupire Urban Village Office. In general, the KKN activities carried out in Paupire Village, Central Ende District, went well because the community response was also good. Planning The implementation of the Mandiri KKN program and activities is expected to be of benefit to the community, especially Entrepreneurship activities in the Paupire sub-district, Ende Tengah Subdistrict, to use business capital properly, to optimize resources for production, and to make good use of marketing.